SPINOPELVIC PARAMETERS AFTER POSTERIOR LUMBAR ARTHRODESIS IN DEGENERATIVE SPINAL DISEASES - Ponte,Julio Alves (2022)
ABSTRACT Introduction: Spinopelvic parameters related to sagittal balance have become increasinglyimportantamong spine surgeons due to their correlation with patient satisfaction rates. Objective: The goal of this study was to evaluate changes in spinal sagittal balance after lumbar spine surgery using PLIF, the posterior lumbar interbody fusion technique. Methods: The sample consisted of adult patients with degenerative spinal disease submitted to posterior lumbar arthrodesis. Patients between 18 and 70 years of agewho underwent surgeryfrom 2015 to 2017 were included in the study and divided into short (1 level) and long arthrodesis (2 to 4 levels) groups. Radiographic analysis of the spinopelvic parameters, measured before and after lumbar arthrodesis, was conducted using the SURGIMAP software. Then we evaluated the variation between pre- and postoperative measurements and performed correlation and linear regression analyses between the parameters. Results: The sample was composed of 80 patients (48 men). The mean age was lower in the short arthrodesis group than in the long arthrodesis group (52.67 ± 9.66 years versus 59.37 ± 9.30 years, respectively; p<0.0025). Significant variations in lumbar lordosis, pelvic tilt, sagittal vertical axis, T1 pelvic angle, and pelvic incidence minus lumbar lordosis were found in both short and long arthrodesis groups. The variation was significantly larger in the long than in the short arthrodesis group. Conclusion: In adult degenerative spine disease, short and long arthrodesis of the lumbar spine by PLIF allows correction of the spinopelvic parameters. Level of evidence III; Retrospective, comparative study.